Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s12519-022-00624-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, treatment, and prevention of monkeypox in children: an experts’ consensus statement

Abstract: Monkeypox is a zoonotic disease. Since the first human monkeypox case was detected in 1970, it has been prevalent in some countries in central and western Africa. Since May 2022, monkeypox cases have been reported in more than 96 non-endemic countries and regions worldwide. As of September 14, 2022, there have been more than 58,200 human monkeypox cases, and there is community transmission. The cessation of smallpox vaccination in 1980, which had some cross-protection with monkeypox, resulted in a general lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…We have identified groups of mild and severe progressors (G1 and G3); the G1 group was characterized by a lower lesion count and more rapid disappearance of lesions, whereas the G3 group exhibited a higher lesion count and slower disappearance of lesions. Our stratification also identified age as a key demographic characteristic affecting lesion dynamics, in accordance with previous studies which suggested that younger age is associated with more likely severe outcomes, which determine the necessity and benefits of hospital-based care [17,27,41].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We have identified groups of mild and severe progressors (G1 and G3); the G1 group was characterized by a lower lesion count and more rapid disappearance of lesions, whereas the G3 group exhibited a higher lesion count and slower disappearance of lesions. Our stratification also identified age as a key demographic characteristic affecting lesion dynamics, in accordance with previous studies which suggested that younger age is associated with more likely severe outcomes, which determine the necessity and benefits of hospital-based care [17,27,41].…”
Section: Discussionsupporting
confidence: 88%
“…Notably, the cutoff value for G1 (i.e., 107 lesion counts) closely matched the boundary between CDC lesion severity categories 2 and 3 (100 lesion counts) [28]. In terms of age categories, children under 5 years old generally exhibited a longer lesion duration and a larger number of lesions, which aligns with previous reports indicating severe lesion symptoms in young children [17,27,41]. 14…”
Section: Quantifying and Stratifying Lesion Transition Dynamics Of Mp...supporting
confidence: 81%
“…Moreover, reducing the time interval between symptom onset and diagnosis is essential for early case detection. Early detection of cases enables prompt intervention to interrupt the chain of transmission, prevent further spread of the disease, and facilitate timely isolation and treatment for patients 13,37 . Additionally, shortening the diagnosis time by increasing testing rates and promoting faster and more effective diagnostic methods will not only improve the efficient utilization of healthcare resources but also reduce the burden of disease on healthcare institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the ongoing global COVID-19 pandemic, Mpox has now surfaced in non-endemic regions in 2022, presenting a new global threat. 1 MPXV is an enveloped, double-stranded DNA virus belonging to the Orthopoxvirus genus of the Poxviridae family, with a genome size of approximately 197 kbps. Under electron microscopy, MPXV appears elliptical, oval, or brick-shaped and measures about 200 nm × 250 nm in size.…”
Section: Introductionmentioning
confidence: 99%